Hubungan Pencahayaan dan Kelembaban dalam Rumah dengan Kejadian Penyakit Tuberkulosis Paru di Wilayah Kerja UPT Puskesmas Kedaton Kota Bandar Lampung: The Relationship Between Indoor Lighting and Humidity with the Incidence of Pulmonary Tuberculosis in the Working Area of UPT Kedaton Public Health Center Bandar Lampung City - Mega Alamzarwati; Khoidar Amirus; Agung Aji Perdana; Iffah Rachmi (LPPM STIKES Guna Bangsa Yogyakarta, 2026)
Background: Pulmonary tuberculosis remains a public health problem in Indonesia, including in the working area of the UPT Kedaton Health Center, Bandar Lampung City. The physical environment of a house, particularly lighting and humidity, is suspected to influence the risk of transmission of this disease. Objective: This study aims to determine the relationship between indoor lighting and humidity in houses and the incidence of pulmonary tuberculosis. Methods: This is a quantitative study with an analytical survey design using a cross-sectional approach. The study population consisted of 2,625 households, with a sample of 335 respondents. Data analysis was conducted using univariate analysis (frequency distribution) and bivariate analysis with the chi-square test. Results: The study found a significant relationship between lighting and the incidence of pulmonary tuberculosis (p-value = 0.030), as well as between humidity and the incidence of pulmonary tuberculosis (p-value = 0.009). Conclusion: The study concludes that poor lighting and high humidity inside houses are associated with an increased risk of pulmonary tuberculosis transmission. Efforts to improve lighting quality and control indoor humidity are needed as part of tuberculosis prevention in residential environments.